Integrasi Regresi dan Anova dalam Mengevaluasi Faktor Penentu Produksi dan Kontribusi Ekonomi Komoditas Perkebunan Tapanuli Selatan - Novita Aswan; Yusra Fadhillah; Rafik Anhar Tambunan; Riky Rivaldo Tambunan (Jurusan Sosial Ekonomi, Fakultas Pertanian, Universitas Andalas, 2025)
This article employs an integrated statistical approach to analyze production determinants and the comparative economic contributions of leading plantation commodities in South Tapanuli Regency (2014-2023). Multiple linear regression indicates that coffee (p=0.033) and cocoa prices (p=0.027) exert a significant positive influence on production, whereas land area demonstrates no significant effect. ANOVA results (F=11.048; p=0.000) reveal statistically significant disparities in contributions to the Regional Gross Domestic Product. Palm oil provides the highest mean contribution (4.66%), which differs significantly from rubber, coffee, and cocoa. No significant difference exists among the latter three commodities. Consequently, this integrated analysis furnishes a robust foundation for policy formulation: implementing price incentives is more efficacious than land expansion for coffee and cocoa development; palm oil necessitates sustainability-focused strategies; and rubber, coffee, and cocoa require product diversification to augment their value-added potential.